Effects of Brain-Derived Neurotrophic Factor on Local Inflammation in Experimental Stroke of Rat - Yongjun Jiang; Ning Wei; Juehua Zhu; Tingting Lu; Zhaoyao Chen; Gelin Xu; Xinfeng Liu (Hindawi Limited, 2010)
This study was aimed to investigate whether brain-derived neurotrophic factor (BDNF) can modulate local cerebral inflammation in ischemic stroke. Rats were subjected to ischemia by occluding the right middle cerebral artery (MCAO) for 2 hours. Rats were randomized as control, BDNF, and antibody groups. The local inflammation was evaluated on cellular, cytokine, and transcription factor levels with immunofluorescence, enzyme-linked immunosorbent assay, real-time qPCR, and electrophoretic mobility shift assay, respectively. Exogenous BDNF significantly improved motor-sensory, sensorimotor function, and vestibulomotor function, while BDNF did not decrease the infarct volume. Exogenous BDNF increased the number of both activated and phagocytotic microglia in brain. BDNF upregulated interleukin10 and its mRNA expression, while downregulated tumor necrosis factor α and its mRNA expression. BDNF also increased DNA-binding activity of nuclear factor-kappa B. BDNF antibody, which blocked the activity of endogenous BDNF, showed the opposite effect of exogenous BDNF. Our data indicated that BDNF may modulate local inflammation in ischemic brain tissues on the cellular, cytokine, and transcription factor levels.